Trends in repeated pregnancy among adolescents in the Philippines from 1993 to 2013 - Maravilla, J.; Betts, K.; Alati, Rosa (BioMed Central Ltd., 2018)
© 2018 The Author(s). Objective: The extent of repeated pregnancy (RP) and repeated birth (RB) among adolescents aged 15-19 is still unknown in the Philippines despite the health and socio-economic consequences. This study aims to investigate the RP and RB prevalence trends in the Philippines from 1993 to 2013. Methods: A total of 7091 women aged 15-24 who experienced at least one pregnancy were captured in the Philippine demographic health surveys from 1993 to 2013. Annual RP and RB prevalence per age group in three and five categories were calculated and stratified by region, type of residence and wealth index. Cochran-Armitage tests and multivariate logistic regression were applied to determine trend estimates. Results: Compared to women aged 19-21 years and 22-24 years, for which decreasing patterns were found, RP ([Adjusted Odds ratio (AOR =0.96; 95%Confidence interval (CI) =0.82-1.11) and RB (AOR = 0.90; CI = 0.73-1.10) trends among 15-18 year olds showed negligible reduction over the 20 years. From a baseline prevalence of 20.39% in 1993, the prevalence of RP among adolescents had only reduced to 18.06% by 2013. Moreover, the prevalence of RB showed a negligible decline from 8.49% in 1993 to 7.80% in 2013. Although RP and RB prevalence were generally found more elevated in poorer communities, no differences in trends were noted across wealth quintiles. Conclusion: For two decades, the Philippines has shown a constant and considerably high RP prevalence. Further investigation, not only in the Philippines but also in other developing countries, is necessary to enable development of secondary prevention programs.